الأمن النفسي و علاقته بالتفكير الايجابي لدى عينة من تلاميذ سنة الثالثة ثانوي - علي واعر دلال; رنان سهيلة; ملياني عبد الكريم (My University, 2018)
The study amied to identify the relation shipe between the pisychologica lsecurity and positive thinkingamong students of the third year secondary , in the city of laghouat to achievethese objectives , a sample of 100 students of the third year secondary was selected in the following dixiplines in (literature , sciences , and economie ) in the secondary city of laghouat it isused:psychometric securityscale" of zainabchocair" and the measure of positive thinking of Ibrahim abdulsattar . after collecting the questionmaire , the data were processed statistically to answer the questions raisedreached the following results. 1) There are correlationsbetweenpsychologicalsecurity and positive thinkingamong of the thridyearsecondary to the city of laghouat. 2) There are not statisticallysignificontdifferences in the psychologicalsecurity variable amongstudents of the thirdyearseciondarythat lead self chomaje (daughters of young ) 3) There are not statisticallysignificantdifferences in positive thinkingamonystudents of the second yearsecondarythat lead to change of specialization . 4) There are not statisticallysignificantdifferences in psychologicalsecurityamongstudents of the thirdyearsecondaryleoding to the variable specialization( scientific / litirature /economy ) 5) There are werstatistically significant differences in positive thinKingamongthrid-year secondarystudent Leard to specialization variable .Scientific/literatur/economy.